The locus of heat resistance (LHR) mediates heat resistance in Salmonella enterica, Escherichia coli and Enterobacter cloacae. (June 2017) - Mercer, Ryan G.; Walker, Brian D.; Yang, Xianqin; McMullen, Lynn M.; Gänzle, Michael G.
Abstract: Enterobacteriaceae comprise food spoilage organisms as well as food-borne pathogens including Escherichia coli . Heat resistance in E. coli was attributed to a genomic island called the locus of heat resistance (LHR). This genomic island is also present in several other genera of Enterobacteriaceae, but its function in the enteric pathogens Salmonella enterica and Enterobacter cloacae is unknown. This study aimed to determine the frequency of the LHR in food isolates of E. coli, and its influence on heat resistance in S. enterica and Enterobacter spp. Cell counts of LHR-positive strains of E. coli, S. enterica and E. cloacae were reduced by less than 1, 1, and 4 log (cfu/mL), respectively, after exposure to 60 °C for 5 min, while cell counts of LHR-negative strains of the same species were reduced by more than 7 log (cfu/mL). Introducing an exogenous copy of the LHR into heat-sensitive enteropathogenic E. coli and S. enterica increased heat resistance to a level that was comparable to LHR-positive wild type strains. Cell counts of LHR-positive S. enterica were reduced by less than 1 log(cfu/mL) after heating to 60 °C for 5 min. Survival of LHR-positive strains was improved by increasing the NaCl concentration from 0 to 4%. Cell counts of LHR-positive strains of E. coli and S. enterica were reduced by less than 2 log (cfu/g) in ground beef patties cooked to an internal core temperature of 71 °C. This study indicates that LHR-positive Enterobacteriaceae pose a risk to food safety. Highlights: The sequence of the LHR is conserved in Enterobacteriaceae . The function of the LHR in providing heat resistance is also conserved. Increasing NaCl improves the survival of LHR-positive E. coli and S. enterica . LHR-positive E. coli and S. enterica survive cooking to 71 °C in ground beef.